A seguir, cenas do próximo capítulo: A construção audiovisual da telenovela brasileira - Ricetto, Leandro Caian Janizelli (2021)
The Brazilian telenovela is one of the most successful and rebound products of the audiovisual industry, despite the changes in production and assistance of serial fiction in recent years, with the rise of streaming platforms and video on demand services. The basis for teledramatúrgic narratives lies in novel and melodrama, so that different telenovelas can present almost identical stories. However, it is the articulation of their constitutive languages, when they enter into syncretism, that gives them different televisual embodiments. This work aims to investigate how the permanence of the serial structure, as an audiovisual construction, in the history of the Brazilian telenovela is manifested. The Discursive Semiotics was the chosen theory for the analysis of the peculiar audiovisual meaning processes of this television format. It should be taken into account its theoretical-methodological device for the study of content and expression. It was opted for a diachronic clipping, with the intention of analyzing the trajectory of the permanence of the novel in its arrangements of audiovisual languages, through the study of scenes of the main plot of five decades, since the beginning of the 70s. Seven telenovelas of Globo Network of urban character were selected: the starting point was Selva de Pedra (1972/1973) and the point of arrival, A Dona do Pedaço (2019). Among the main findings with the research, it was observed that there is a specific audiovisual pattern for the plane of expression, of a Brazilian know-how, followed by the telenovelas – and that not only the modifications in its syncretic arrangement (such as the acceleration of rhythm, thinking about the decrease in the duration of scenes and planes), as well as maintenance (American shot and close-up to focus the characters and spaces where they are; in addition to the spoken verbal language overlap with the soundtrack and the other plastic formants) incorporated into each telenovela that guarantee the permanence of the televisual serial. The triadic structure defended by Jesús Martín-Barbero (victim, punisher and traitor) is only a protagonist/victim and villain/traitor, who end up absorbing the roles of punisher and silly, respectively. In addition, it was noted that rhythm is the regent element in relation to the kinetic formant and the other sound and visual formants in the process of syncretism of telenovelas over the decades